Gramaticalização de orações avaliativas completivas do verbo achar - Parreira, Ana Caroline de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The proposed work addresses the non-verbal predication embedded in the verb to think aiming to discuss the status of embedded predication, from the point of view of grammaticalization (HOPPER; TRAUGOTT, 2003; LEHMANN, 1988). It is known and fairly investigated in Portuguese complex sentences composed by predicates that indicates evaluation and modality in which embed a non-verbal predication, as in I think [that your hair is beautiful]. We are interested, however, in the investigation of the complex sentence, in which an evaluative predication structured by the verb think, fits a reduced non-verbal predication without use of copular verb, as in I think [this chair to be comfortable], a complex sentence strongly integrated in syntactic, semantic and pragmatic terms when it contrasts this kind of predication to its counterparty expanded I think [that this chair is comfortable]. Through the analysis of samples of Portuguese spoken selected in Iboruna database (GONÇALVES, 2007), it was conducted an investigation of syntactic, semantic and pragmatic motivations in order to present a description of the behavior of the predicates in study. In addition, the present research, from a synchronic perspective, provides evidence for the process of grammaticalization of non-verbal predication embedded in the verb think, based on the continuum of grammaticalization and desententialization proposed by Lehmann (1988). The survey results reveal that the employment of non-verbal predicates reduced signals a speaker evaluation due to their direct experience with the source of the evaluation while expanded predication indicates an evaluation based on an experience obtained indirectly by the speaker. The comparative analysis of non-verbal predicates and developed attests that the reduced non-verbal predication are more integrated thab expanded predication, which culminated in the development of a continuum of grammaticalization from the scale proposed by ...

O trabalho proposto aborda as predicações não-verbais reduzidas avaliativas encaixadas no verbo achar, com o objetivo de discutir o estatuto da predicação encaixada, do ponto de vista da gramaticalização (HOPPER; TRAUGOTT, 2003; LEHMANN, 1988). São conhecidas e bastante investigadas na língua portuguesa orações complexas compostas de predicado matriz avaliativo ou modalizador no qual se encaixa uma oração na forma finita, como em “Acho [que o seu cabelo é lindo]”. Interessa-nos, no entanto, a investigação do complexo oracional em que, em uma predicação avaliativa em que figura o verbo achar, encaixa-se uma predicação não verbal reduzida, estruturada por um predicador adjetival avaliativo sem recurso à cópula, como em “Acho [essa cadeira confortável / confortável essa cadeira]”, um complexo oracional fortemente integrado do ponto de vista sintático, semântico e pragmático, quando se contrasta esse tipo de predicação reduzida a sua contraparte desenvolvida “Acho que [essa cadeira é confortável / é confortável essa cadeira]. Por meio da análise de amostras do português falado no interior paulista selecionadas do banco de dados Iboruna (GONÇALVES, 2007), procedeu-se a uma investigação das motivações sintáticas, semânticas e pragmáticas a fim de apresentar uma descrição do comportamento das predicações em estudo. Além disso, a presente pesquisa investiga, a partir de uma perspectiva sincrônica, o processo de gramaticalização das predicações não-verbais reduzidas avaliativas encaixadas no verbo achar, com base na escala de gramaticalização de orações proposta por Lehmann (1988). Os resultados da pesquisa revelam que o emprego das predicações nãoverbais reduzidas sinaliza uma avaliação do falante decorrente de sua experiência direta com a fonte da avaliação ao passo que as desenvolvidas indicam uma avaliação pautada em uma experiência obtida indiretamente pelo falante ...
Keywords: Linguística; Língua portuguesa - Gramaticalização; Língua portuguesa - Construções subordinadas; Gramatica comparada e geral - Verbo; Língua portuguesa - Portugues falado - São José do Rio Preto, Região de (SP); Linguística de corpus; Linguistics